Pemanfaatan Quizizz Sebagai Media Penilaian Pembelajaran Bahasa Inggris - Syafaruddin Marpaung (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This study aims to analyze the implementation of assessment learning outcomes using Quizizz at SMA Negeri 2 Tanjungbalai. The results of this study indicate that the use of quizizz as a learning outcome assessment media during the Covid-19 period includes three stages. The first stage is the planning stage, which includes the policy on the use of quizizz, preparation of human resources and facilities, socialization, and design of the use of quizizz. The second stage, namely the implementation stage, includes the implementation of daily assessments and mid-semester assessments. The third stage is about making decisions on learning outcomes with quizizz. Based on these results, it can be concluded that the use of quizizz as a media for assessing results during the Covid-19 period at SMA Negeri 2 Tanjungbalai is very effective because during the Covid-19 pandemic learning is overall done online, quizizz as an online learning medium can be accessed anywhere, anytime, and by anyone, students and educators as admins can immediately see the score of learning outcomes. In addition, learning outcomes can be directly downloaded in the form of an excel file, making it easier and faster for teachers to make decisions about learning outcomes for students. Keywords: assessment; learning media; Quizizz Abstrak: Penelitian ini bertujuan untuk menganalisis pelaksanaan penilaian hasil belajar menggunakan Quizizz di SMA Negeri 2 Tanjungbalai. Hasil penelitian ini menunjukan bahwa pemanfaatan quizizz sebagai alat penilaian hasil belajar dalam masa Covid-19 meliputi tiga tahap. Tahap pertama adalah tahap perencanaan, meliputi kebijakan pemanfaatan quizizz, persiapan SDM dan sarana, sosialisasi, dan desain pemanfaatan quizizz. Tahap kedua yakni tahap pelaksanaan, meliputi pelaksanaan penilaian harian dan penilaian tengah semester. Tahap ketiga tentang pengambilan keputusan hasil belajar dengan quizizz. Berdasarkan hasil tersebut dapat disimpulkan bahwa pemanfaatan quizizz sebagai alat penilaian hasil dalam masa Covid-19 di SMA Negeri 2 Tanjungbalai sangat efektif karena pada masa pandemi Covid-19 pembelajaran secara keseluruhan dilakukan secara daring, quizizz sebagai media belajar online dapat diakses di manapun, kapanpun, dan oleh siapapun, peserta didik dan pendidik sebagai admin dapat langsung melihat skor hasil belajar. Selain itu, hasil belajarpun dapat langsung diunduh dalam bentuk file excel, memudahkan dan mempercepat guru dalam mengambil keputusan hasil belajar terhadap peserta didik. Kata kunci: media; penilaian pembelajaran; Quizizz